An Introduction to scientology an exclusive interview with L. Ron Hubbard - Hubbard, L. Ron (La Fayette Ron) 1911-1986. ([Los Angles, Calif.] Golden Era Productions, 2006)
An interview with L. Ron Hubbard in which he discusses the basic principles of scientology.
Filmed in Salisbury, Rhodesia (now Zimbabwe), in May 1966 by Rhodesian Television. (from program booklet)
Interview took place in April 1966.
Keywords: Hubbard, L. Ron -- 1911-1986.; Dianetics; Scientology